THE RELATIONSHIP BETWEEN STUDENT LEARNING STYLE AND INTENSITY OF MATHEMATICS LEARNING WITH MATHEMATICS LEARNING OUTCOMES IN CLASS VIII - Rizka Wulandari; Edi Prajitno (AdMathEduSt: Jurnal Ilmiah Mahasiswa Pendidikan Matematika, 2019)
Based on observations and interviews in Junior High School (SMP) Muhammadiyah Piyungan known that students have not known the learning style according to each student and student learns mathematics if the test will be held only. This study aims to determine whether or not a positive and significant relationship between student learning styles and intense mathematics learning with the results of learning Mathematics Students in Class VIII SMP Muhammadiyah Piyungan the second semester in the Year 2017/2018. This study's population was all class VIII students, even semester classes SMP Muhammadiyah Piyungan excellent school year  2017/2018, which consisted of class VIII A, VIII B and VIII C which 69 students in total. The sample was taken with a random sampling technique and derived class VIII A. Technique of data collection is done by using questionnaires to the learning style and intense of mathematic learning. While the result of learning mathematics using test instruments. Test of research instrument includes a validity test, a test of different power, and reliability test. The prerequisite analysis test includes the normality test, linearity test, and independence test. Data analysis using product moment analysis and multiple linear regression analysis. The results showed a positive and significant relationship between students' learning style with the results of learning Mathematics Students in Class VIII grade high school student at SMP Muhammadiyah Piyungan in the second semester in the year of 2017/2018. It is announced by  or 3,1057 > 2,0796. Simple correlation coefficient (r) between student learning styles with mathematics learning result of 0,5610 with Ŷ =  -98,742 + 2,2306 X1. There was a positive and significant relationship between mathematics learning's intence with the results of learning Mathematics Students in Class VIII grade high school student at SMP Muhammadiyah Piyungan in the second semester in the year of 2017/2018. It is announced by  or 3,9954 > 2,0796. The simple correlation coefficient (r) between the intence of mathematics learning with mathematics learning result of 0,6571 with  = -18,32 + 1,121 X2.  There was a positive and significant relationship between students' learning style and the intensity of mathematics learning with the results of learning Mathematics Students in Class VIII grade high school student St SMP Muhammadiyah Piyungan in the second semester of the year of 2017/2018. It is announced by  that is 11,228 > 3,4900 with R = 0,727278723 and R2 = 0,5289343 40 with Ŷ = -93,430838784 + 1,368097961 X1 + 0,872373868 X2 with RC1 = 36,49% and RC2 = 63.50%. While for EC1 = 19,30% and EC2 = 33,58%.